A Relationship Between Price and Quality Rating of Wines From the Czech Republic. Issue 2 (3rd April 2017) - Zelený, Jiří
ABSTRACT: This report focuses on the relationship between the prices of wines and quality measured on a 100-point quality scale. Only wines from the Czech Republic evaluated during the first round of the Prague Wine Trophy 2015 competition were included in this study. In total, 114 wine samples from five wine categories were examined. Two types of statistical methods were used to obtain results. Chi-square test of independence in contingency table did not show any statistically significant relationship between the commonly used price categories and the quality of wines expressed as medal awards obtained in the competition. Correlation coefficient was used to examine the relationship between price and quality within individual categories of wines. Medium correlation was found in the categories of white cuvée and sparkling wines, and moderate correlation was observed in the Blaufränkisch category. For the category with the highest value of correlation coefficient, regressive function was formed.